DAMPAK COVID 19 TERHADAP HARGA SAHAM DAN VOLUME TRANSAKSI - Annisa Regina Hartanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
The rapid spread of the Covid-19 outbreak had an impact on the entire world economy, including in Indonesia. This research aims to analyze whether there are significant differences in stock prices and transactions volume in automotive manufacturing companies due to the Covid-19 pandemic. This research data was collected for thirty-one days before and after the announcement of the Covid-19 virus in Indonesia. Processing the data using the paired sample t-test, through SPSS version 23. The results of the data processing show that there is a significant difference in stock prices before and after the announcement of the Covid-19 case. Stock prices are lower than before the Covid-19 case. The transaction volume is known to have a significant difference.